Macbeth : A Play - Shakespeare, William (UK Cambridge University Press, 2007)
These popular Shakespeare editions attractively presented and designed to make Shakespeare relevant to students. The plays are initially summarised in lively line illustrations that present the story in pictures to assist students to recognise the plot and major issues.
Include Illustration
Keywords: Macbeth (Shakespeare, William) -- English drama--Early modern and Elizabethan -- English drama